ОСОБЕННОСТИ ЛЕКСИКОГРАФИРОВАНИЯ МНОГОЗНАЧНЫХ СЛОВ В «ЦЕРКОВНОМ СЛОВАРЕ» ПРОТОИЕРЕЯ ПЕТРА АЛЕКСЕЕВА - Феликсов, Сергей (Acta Neophilologica, 2017)
This article discusses features of the lexicographic description of polysemous words in one of the most valuable works in eighteenth-century Russian culture – The Church Glossary by Archpriest Peter Alekseev. It is the first work in the history of Russian lexicography that provides the most comprehensive description of church terms.